2007
DOI: 10.1111/j.1365-2141.2007.06679.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent venous thromboembolism during coumarin therapy. Data from the computerised registry of patients with venous thromboembolism

Abstract: must be at least some other mechanisms platelet dysfunction that influence the risk of bleeding. As long as the molecular mechanisms of dysplasia and dysfunction of platelets in MDS are unknown, we can only rely on platelet counts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 10 publications
1
15
0
1
Order By: Relevance
“… 11 This must, however, be considered against the annual risk of arterial thromboembolism in the absence of OAC therapy, which is 12% to 22% for patients with mechanical heart valves, and 6% to 18% in patients with AF plus a CHA 2 DS 2 -VASc score of ≥3, and there is a 5% to 7% risk of VTE recurrence in the first 3 months for patients receiving OAC for previous VTE. 40 43 The clinical consequences of a thrombotic or bleeding event must also be taken into consideration when deciding to restart OACs. For example, mechanical heart valve thrombosis is fatal in approximately 12% of patients, embolic stroke results in death in up to 27% of cases, while VTE has a case-fatality rate of approximately 4% to 14%, and major bleeding has a case-fatality rate of approximately 9% to 13%.…”
Section: Risk Stratification and Clinical Decision-makingmentioning
confidence: 99%
“… 11 This must, however, be considered against the annual risk of arterial thromboembolism in the absence of OAC therapy, which is 12% to 22% for patients with mechanical heart valves, and 6% to 18% in patients with AF plus a CHA 2 DS 2 -VASc score of ≥3, and there is a 5% to 7% risk of VTE recurrence in the first 3 months for patients receiving OAC for previous VTE. 40 43 The clinical consequences of a thrombotic or bleeding event must also be taken into consideration when deciding to restart OACs. For example, mechanical heart valve thrombosis is fatal in approximately 12% of patients, embolic stroke results in death in up to 27% of cases, while VTE has a case-fatality rate of approximately 4% to 14%, and major bleeding has a case-fatality rate of approximately 9% to 13%.…”
Section: Risk Stratification and Clinical Decision-makingmentioning
confidence: 99%
“…The risk of VTE recurrence is present even during anticoagulant therapy. An overall rate of 5.5% of recurrent VTE during the initial 3 months of anticoagulant treatment was found in one study [11] and of 7.0% in the very large cohort of patients included in the RIETE registry [16]; in the latter study patients with recurrence during VKA treatment were more frequently males, younger, and with a higher incidence of cancer than those without recurrence [16]. …”
Section: Incidence Of Vte Recurrencementioning
confidence: 99%
“…According to the Virchow's triad, VTE is a condition that results from altered blood coagulation, stasis or abnormalities in the vessel wall [11,12]. Previous studies have identified multiple risk factors for VTE, including age, previous VTE episodes and cerebrovascular disease (CVA) [13][14][15]. Diabetes, leg fractures, major surgery and certain cancers are also associated with increased risk of VTE [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%